The Education Activity of Daily Living in Preventing Neck and Arm Pain in Housewives - Hendrik, Hendrik; Arpandjam'an; Hakim, Supartina (PT Inovasi Pratama Internasional, 2024)
Introduction: Everyone, especially housewives, has daily activities that must be completed, such as waking up and so on. Therefore, daily activities or activities need to be managed properly and correctly so as not to cause health problems, especially neck and arm pain. Objective: This community service project aims to improve the knowledge and ability of partners in carrying out daily tasks at work to reduce arm and neck pain. Method: The technique used is partner counseling and mentoring. The partners or participants involved were 40 housewives domiciled in Berua and Tamalanrea Districts, Makassar City who did not work as civil servants or private employees. Results: The results of the study before being given counseling and mentoring showed that 33 people (82.5%) had insufficient knowledge and skills, 5 people (12.5%) had sufficient knowledge and 2 people (5%) had good knowledge, and after receiving counseling and mentoring none had insufficient knowledge and skills, 9 people (22.5%) had sufficient knowledge and 31 people (77.5%) had good knowledge. Conclusion: counseling accompanied by activity support can increase mothers' understanding of how to prevent neck and arm pain.